Special Edition Vol. 2 No. 12 (CONOCIMIENTO, INVESTIGACIÓN Y EDUCACIÓN CIE, 2021)
The end of life is the beginning of a new story, the true meaning of living eternally with God and with those who preceded us. Without a doubt, in recent years humanity has had to experience rapid changes caused by one of the worst pandemics to strike the world, which led us to live through events for which no one was prepared (lockdowns and social isolation, decreased human mobility, economic, educational, and cultural paralysis, and the accelerated or premature departure of loved ones), among others.